Impact of telemedicine on glycemic control in type 2 diabetes mellitus during the COVID-19 lockdown period - Al-Mutairi, Abrar M.; Alshabeeb, Mohammad A.; Abohelaika, Salah; Alomar, Fadhel A.; Bidasee, Keshore R. (Frontiers in Endocrinology, 2023)
Background The lockdown at the start of coronavirus disease 2019 (COVID-19) pandemic in Saudi Arabia (March 2020 to June 2020) shifted routine in-person care for patients with type 2 diabetes mellitus (T2DM) to telemedicine. The aim of this study was to investigate the impact telemedicine had during this period on glycemic control (HbA1c) in patients with T2DM Methods 4,266 patients with T2DM were screened from five Ministry of National Guard Health Affairs hospitals in the Kingdom of Saudi Arabia. Age, gender, body mass index (BMI), HbA1c (before and after the COVID-19 lockdown), duration of T2DM, comorbidities and antidiabetic medications data were obtained. Mean and standard deviation of differences in HbA1c were calculated to assess the impact of telemedicine intervention. Correlations between clinically significant variances (when change in the level is ≥0.5%) in HbA1c with demographics and clinical characteristic data were determined using chi square test. Results Most of the participants were Saudis (97.7%) with 59.7% female and 56.4% ≥60 years of age. Obesity was 63.8%, dyslipidemia 91%, and hypertension 70%. Mean HbA1c of all patients slightly rose from 8.52% ± 1.5% before lockdown to 8.68% ± 1.6% after lockdown. There were n=1,064 patients (24.9%) whose HbA1c decreased by ≥0.5%, n =1,574 patients whose HbA1c increased by ≥0.5% (36.9%), and n =1,628 patients whose HbA1c changed by <0.5% in either direction (38.2%). More males had significant improvements in glycemia compared to females (28.1% vs 22.8%, p<0.0001), as were individuals below the age of 60 years (28.1% vs 22.5%, p<0.0001). Hypertensive individuals were less likely than non-hypertensive to have glycemic improvement (23.7% vs 27.9%, p=0.015). More patients on sulfonylureas had improvements in HbA1c (42.3% vs 37.9%, p=0.032), whereas patients on insulin had higher HbA1c (62.7% vs 56.2%, p=0.001). HbA1c changes were independent of BMI, duration of disease, hyperlipidemia, heart and kidney diseases. Conclusion Telemedicine was helpful in delivering care to T2DM patients during COVID-19 lockdown, with 63.1% of patients maintaining HbA1c and improving glycemia. More males than females showed improvements. However, the HbA1c levels in this cohort of patients pre- and post-lockdown were unsatisfactorily high, and may be due to in part lifestyle, age, education, and hypertension.